1998
DOI: 10.1515/jpme.1998.26.4.284
|View full text |Cite
|
Sign up to set email alerts
|

Lack of benefits of left tilt in emergent cesarean sections: A randomized study of cardiotocography, cord acid-base status and other parameters of the mother and the fetus

Abstract: No benefits were found in performing cesarean section in left lateral tilt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 12 publications
2
13
0
1
Order By: Relevance
“…106 Two studies found no improvement in maternal hemodynamic or fetal parameters with 10°to 20°left-lateral tilt in patients not in arrest. 107,108 One study reported more aortic compression at 15°l eft-lateral tilt compared with a full left-lateral tilt. 97 In addition, aortic compression has been found at Ͼ30°of tilt, 109 however the majority of these patients were in labor.…”
Section: Resuscitation Of the Pregnant Patient In Cardiac Arrest (Figmentioning
confidence: 99%
“…106 Two studies found no improvement in maternal hemodynamic or fetal parameters with 10°to 20°left-lateral tilt in patients not in arrest. 107,108 One study reported more aortic compression at 15°l eft-lateral tilt compared with a full left-lateral tilt. 97 In addition, aortic compression has been found at Ͼ30°of tilt, 109 however the majority of these patients were in labor.…”
Section: Resuscitation Of the Pregnant Patient In Cardiac Arrest (Figmentioning
confidence: 99%
“…The first compares the left or right tilted supine position with the full left lateral position. 14-17 The second compares lateral or tilted supine positions with the complete supine position, [18][19][20][21] and the third compares different locations of wedges or right-tilted vs. left-tilted positions. 22,23 The current study could be classified in the last of these three groups because it compared the use of a lumbar-pelvic wedge with the complete supine position.…”
Section: Discussionmentioning
confidence: 99%
“…448 Two studies found no improvement in maternal hemodynamic or fetal parameters in nonarrest patients with 10 to 20°left lateral tilt. 449,450 One study found more aortic compression at 15°left lateral tilt when compared to a full left lateral tilt. 442 In addition, aortic compression has been found to persist at over 30°of tilt; 451 however, the majority of these patients were in labor.…”
Section: Aortocaval Decompression To Improve Maternal Hemodynamics Anmentioning
confidence: 99%